A Psychosocial Exploration of Love and Intimacy - Brown, J. author. aut Link
VIII, 258 p.
Keywords: Organised around a single question: is love possible?, Brown's book provides conceptualisations of love and its possibility from sociological, philosophical and psychoanalytic viewpoints. She argues for the importance of a psychosocial understanding of love and provides a critical discussion of the philosophy and methods of Psychosocial Studies.